Determinants Of Stock Returns and Their Implications for Dividend Policy of Mining Sector Companies on The Indonesian Stock Exchange - Kusmanto, Kusmanto (Journal of Economics and Management Scienties, 2025)
This study analyzes the influence of fundamental microeconomic and macroeconomic factors on stock returns and their implications for the dividend policy of mining sector companies listed on the Indonesia Stock Exchange during 2019–2024. Microeconomic variables include operational cash flow, working capital, and net income, while macroeconomic variables comprise the interest rate (BI Rate) and the rupiah exchange rate (KURS). This research uses a quantitative approach with an associative method. The results show that working capital, net income, interest rates, and exchange rates significantly and positively affect stock returns, while operational cash flow has no significant effect. This indicates that investors prioritize profitability and capital efficiency over short-term cash flow. Regarding dividend policy, working capital, net income, interest rates, exchange rates, and stock returns significantly and positively influence dividend payouts. Operational cash flow, however, shows no significant impact, suggesting companies base dividend decisions more on profitability and macroeconomic conditions. Simultaneously, all studied micro and macro variables significantly affect stock returns and dividend policy. These findings emphasize that internal financial performance and external economic indicators are key considerations in investment decisions and dividend formulation. The study implies that companies should focus on profitability and efficient working capital management while accounting for macroeconomic trends to develop sustainable dividend policies. For investors, understanding both internal company performance and broader economic factors is crucial for rational investment choices.